1988
DOI: 10.1104/pp.88.2.329
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Production by Attached Leaves or Intact Shoots of Tobacco Cultivars Differing in Their Speed of Yellowing during Curing

Abstract: Using an open air flow system, differences in the yellowing rate of leaves during curing were assessed in relation to ethylene production by shoots of intact seedlings or attached mature leaves of 60 day old tobacco (Nicotiana tabaum L.) plants. The rate of ethylene evolution from the leaves of the fast yellowing cultivars was significantly higher than in the slow yellowing ones. The same differences were obtained with shoots of intact seedlings. The findings suggest that it is possible to use ethylene product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Several reports have demonstrated that ethylene production in attached or detached leaves of various species increased during senescence or in response to exogenous ethylene in a climacteric-like pattern (Aharoni et al, 1979;Alejar et al, 1988;McGlasson et al, 1975;Morgan and Durham, 1980;Gepstein and Thimann, 1981;Riov and Yang, 1982;Morgan et al, 1992). A similar phenomenon was observed in leaf discs following wounding and particularly in response to ethylene treatment (Aharoni et al, 1979;Riov and Yang, 1982).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Several reports have demonstrated that ethylene production in attached or detached leaves of various species increased during senescence or in response to exogenous ethylene in a climacteric-like pattern (Aharoni et al, 1979;Alejar et al, 1988;McGlasson et al, 1975;Morgan and Durham, 1980;Gepstein and Thimann, 1981;Riov and Yang, 1982;Morgan et al, 1992). A similar phenomenon was observed in leaf discs following wounding and particularly in response to ethylene treatment (Aharoni et al, 1979;Riov and Yang, 1982).…”
Section: Introductionmentioning
confidence: 67%
“…In general, leaves evolve increased levels of ethylene during natural senescence as they do after detachment (Aharoni et al, 1979;Alejar et al, 1988;McGlasson et al, 1975;Morgan and Durham, 1980;Gepstein and Thimann, Fig. 4.…”
Section: Two Systems Of Ethylene Production Are Operating In Citrus Leavesmentioning
confidence: 95%
“…Abscission of fruits can be promoted by ethylene (Sexton et al, 1985;Henderson & Osborne, 1994) and it is well documented that stomatal closure can be induced by ABA (Jones & Mansfield, 1970;Zhang, Schurr & Davies, 1987;Davies & Jones, 1991). Leaf senescence can be promoted by ethylene (Alejar, Viser & Spencer, 1988;Matoo & Aharoni, 1988;Aharoni, 1989) and ABA (Nooden, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors influence industrial utilization and the style of the tobacco leaf and include the ecological environment, cultivar, maturity, agronomic management, and curing technology (Reed et al, 2012). Among these factors, the yellowing stage in the flue-curing process is a key step during which complex physical, physiological, and biochemical reactions materialize in the tobacco leaves (Bacon et al, 1952;Weston, 1968;Koiwai and Kisaki, 1979;Alejar et al, 1988). Previous studies have focused on various aspects of the curing process for flue-cured tobacco leaves, including temperature, humidity, time, and draft fan control (Zhan et al, 2011;Cui et al, 2013;Xie et al, 2013).…”
Section: Introductionmentioning
confidence: 99%